Hormetic effect of UV-C radiation on red mustard microgreens growth and chemical composition
Brassica microgreens are rich in phytochemicals and are attractive crops for controlled vertical farming systems where the light spectrum can be precisely manipulated. Understanding the effects of pre-harvest hormetic UV-C light doses on plant composition and growth parameters represents a novel and largely unexplored area for precision agriculture and nutrition. Therefore, the objective of this work was to investigate the impact of exposing red mustard microgreens to low/hormetic doses of UV-C radiation on their growth, chemical composition and colour. Plants were grown in a controlled environment and exposed to 0.3 kJ m(-2), 254 nm UV-C radiation at the end of the cultivation period. Treatments included a single pulse on day 7, or three pulses at days 7, 8, and 9 and harvest on day 10. UV-C radiation presented a hormetic effect, while 1 pulse of UV-C stimulated growth and productivity without significant colour changes in microgreens, 3 pulses of UV-C radiation to did not show significant effects when compared to controls (no UV-C exposure). Moreover, strong negative correlations were observed between growth parameters and chemical composition (p < 0.05). Microgreens with enhanced growth parameters showed a decrease in phenolic compounds content and antioxidant activity. Interestingly, regardless of quantification, untargeted metabolomics using UHPLC-Q-Orbitrap-MS/MS revealed that the secondary metabolites profile remained similar between control and microgreens treated with UV-C radiation.